2016
DOI: 10.18585/inabj.v8i1.196
|View full text |Cite
|
Sign up to set email alerts
|

Lung Function Status of Workers Exposed to Welding Fume: A Preliminary Study

Abstract: B ACKGROUND:Exposure to welding fume in the workplace was associated with lung function disorders and occupational asthma. In this study, we determined lung function parameters in men workers exposed to welding fumes from heavy equipment manufacturer. This study is a preliminary study of biomonitoring program in worker exposed to welding fume as our main study. METHODS:A study with case-control design, random study, was conducted among welder (59 subjects) and nonwelder (34 subjects) with more than one year ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Compared with gases, noise, heat, and the ultraviolet radiation, fumes produced during the welding process have the most deleterious effects on the welders' health. 1,2 Approximately, 500000 full-time employees are working in the US in the capacity of welding operators. 3 There are 5.5 million welding-related businesses in the Europe.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with gases, noise, heat, and the ultraviolet radiation, fumes produced during the welding process have the most deleterious effects on the welders' health. 1,2 Approximately, 500000 full-time employees are working in the US in the capacity of welding operators. 3 There are 5.5 million welding-related businesses in the Europe.…”
Section: Introductionmentioning
confidence: 99%
“…It is believed that the presence of these contents has negative effects on the environment, particularly human health. Welders over a long period can have over exposure to manganese in their body or other elements, occupational asthma, and lung disorders [19,20]. Furthermore, the SMAW shows a better reduction of global warming than TIG through reducing CO2 emissions [21].…”
Section: Resultsmentioning
confidence: 99%
“…Results from stratification of welding doses over many years also showed different degrees of damage to lung function, which was attributed primarily to an obstructive pattern of airway disease [27]. Working period is an important indicator for evaluation of lung function status among welders [28]. The results showed that of 14 respondents who worked more than five years (at risk), there were five respondents who did not experience impaired lung capacity (normal).…”
Section: Correlation Of Individual Factors With Lung Function Reducti...mentioning
confidence: 98%
“…The data showed that nine respondents (69.2%) who did not use PPE experienced reduced lung function. Welders' adherence to using personal protective equipment is also different from other welders even in their working time [28]. PPE is used to prevent occupational accidents and subsequent health problems.…”
Section: Correlation Of Behavioral Factors With Lung Function Reducti...mentioning
confidence: 99%